Referendum w obliczu głosowania za pośrednictwem Internetu – doświadczenia Estonii, Norwegii i Szwajcarii - Rzucidło, Jakub (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
In the article author addresses the issue of the use of voting via the Internet in a referendum in the Polish Republic. This problem is analyzed in view of the experiences of three European countries (Estonia, Norway and Switzerland) with the application of that method of voting in both elections (national and local), and in the referendum. Such analysis helps to predict what risks and benefits would be the possible if i-voting in a referendum were introduced. Moreover author presents the impact of the introduction of such voting method on turnout in the referendum. These considerations led to examine possibilities, chances and risks for the use of i-vote in the referendum in the Polish Republic.
Keywords: referendum ogólnokrajowe; e-voting; referendum lokalne; frekwencja; internet; i-głosowanie; głosowanie; i-voting; ID card